The Role of Biodegradable Magnesium and Its Alloys in Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis Based on Animal Studies - Shang, Zhizhong; Li, Dongliang; Chen, Jinlei; Wang, Mingchuan; Zhang, Baolin; Wang, Xin; Ma, Bin (Frontiers in Bioengineering and Biotechnology, 2021)
Abstract Objective The actual efficacy of magnesium and its alloy in anterior cruciate ligament reconstruction (ACLR) was systematically evaluated to reduce the risk of translation from animal experiments to the clinic. Methods Databases of PubMed, Ovid-Embase, Web of science, CNKI, Wanfang, VIP, CBM were searched for literature in July 2021. Screening of search results, data extraction, and literature quality evaluation were undertaken independently by two reviewers. Results and Discussion Seven articles were selected for the meta-analysis. The results showed that magnesium and its alloys not only have the same mechanical properties as titanium and its alloys, but also perform better in promoting new bone formation. In addition, the unique biodegradability makes magnesium and its alloys an orthopedic implant with significant therapeutic potential. However, whether the degradation rate of magnesium and its alloy can match the rate of bone-tendon integration, and whether the biocombination of bone-tendon after degradation can meet the exercise load still needs to be explored in further detail. Simultaneously, it is necessary for future research to improve and standardize experimental design and result measurement, etc., so as to minimize the risk of transforming animal experimental results into clinical practice.